Noticing, assessing, and responding to students' engineering: Exploring a responsive teaching approach to engineering design. - Wendell, Kristen.; Watkins, Jessica.; Johnson, Aaron W. (Tufts University. Tisch Library., 2017)
This research paper describes a study of the disciplinary substance of formative assessment for engineering design learning. Borrowing the framework of responsive teaching from the math and science education literature, we argue for the importance of closely examining the many moment-to-moment decisions that engineering teachers face. Responsive teaching is an instructional approach in which instructors base their pedagogical moves on what their students are saying and doing. Instead of predetermining what will happen in classrooms, teachers focus on eliciting students' ideas, interpreting disciplinary aspects of students' reasoning, and responding with pedagogical decisions based on these interpretations. Responsive teaching has the potential to be a particularly useful approach for teaching engineering design: As students adapt to new criteria and constraints when solving ill-defined engineering design problems, teachers need to be responsive to their changing needs. However, most of the work on responsive teaching has occurred in math and science education. In this paper, we follow in the tradition of math and science education researchers who use their own teaching episodes as the basis for scholarly research on responsive teaching. Using microgenetic analysis, we examined two video-recorded cases from our engineering teaching to explore how different yet equally legitimate disciplinary goals can conflict with each other and produce "instructional tensions" for the teacher. We used purposeful sampling to select cases rich in opportunities to unpack formative assessment information through a responsive teaching lens. We present in-depth analyses of the tensions that emerged between different disciplinary goals in STEM learning environments. These results point to the need for increased attention on how teachers manage the different disciplinary practices and goals in STEM activities, particularly when incorporating formative assessment strategies or adopting a responsive teaching approach.